Shorter wavelength gain shift in EDFA using a macro-bending approach - Daud, S. A.; Mohamed, Khalid Sheikhidris; Abdul Rashid, Hairul Azhar; Mokhtar, Mohd Ridzuan; Yusoff, Zulfadzli; Abd Rahman, Faidz; Emami, Siamak Dawazdah; Harun, Sulaiman Wadi; Ahmad, Harith (IEEE, 2008)
Gain and noise figure improvements are demonstrated in a shorter wavelength region of double-pass EDFA using a macro-bending approach. The EDIT is wound in a small radius to suppress the amplified spontaneous emission at the longer wavelength in order to achieve a high amplification in the shorter wavelength. Gain enhancements of about 12 similar to 14 dB are obtained with macro-bending at wavelength region between 1480 nm and 1530 nm. The micro-bending also reduces the noise figure of the EDFA at wavelengths shorter than 1525nm with maximum improvement of 25 dB.